(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of nursing students participating in an educational action, carrying out health educational activities with women aged 25 to 64 years, at the ESF Mangueirão regarding early screening for cervical cancer, the participating group was composed by 9 women. Method: this is a quantitative, descriptive study, of the experience report type. Result: The action was developed after collecting data on the subject, through the strategies of concisely explaining the theme, for the development of the action an educational instrument was developed in the form of a banner with important information on the subject and a dynamic interactive questions and answers with the help of signs with positive and negative signs, evidently signaling the participants’ understanding of the topic addressed. Conclusion: in this way, through the educational activity carried out, we obtained great participation from the target audience, raising doubts about cervical cancer, Pap smears and also issues related to sexuality and the female body. The activity takes place in an expository/participatory way, with great learning by the academic team as well as for a target population.